Sensitivity of infrared sensor faucet on different skin colours and how it can potentially effect equity in public health - Qi Ren, Xiao; BCIT School of Health Sciences, Environmental Health; Heacock, Helen (BCIT Environmental Public Health Journal, 2022)
Hand hygiene is essential to human health and day-to-day activities. Maintaining proper hand hygiene can help reduce pathogen growth and transmission of diseases. The automated sensor used for bathroom faucets and soap dispensers can be dated back to the 1950s. These types of fixtures are usually equipped with sensors using a near-infrared beam to detect hands. Its introduction has improved hand hygiene and facilitated good handwashing behaviour. At the same time, disadvantages that come along with advanced technologies should not be neglected, and these disadvantages may lead to inequity in the society.